The Importance of Green Supply Chain Management and Its Role in Marketing Management - Shahriarpour, Moujan; Tabriz, Akbar Alam (International Journal of Economics and Financial Issues, 2017)
Supply chain is a network of organizations that in connection with those upstream to downstream are involved in the processes and activities and they produce value to the final customer in the goods and provided services. This subject on its own figured new challenges out for them. The chain management is offering a complex of methods used in integrating the providers, producers, barns and stores in order to produce and offer the intended products on a specified amount, in a certain time and in a specified place. This caused the whole chain expenses be decreased, in addition the customers’ needs be met with high service level. In this study, first of all the history of the emergence of supply chain and continue to components and elements and how the evolution of the green supply chain management will be discussed. The aim of this issues and literature related to green supply chain and understand its importance in the production of goods for all researchers, manufacturers and marketing. Keywords: supply chain, green supply chain management, marketing JEL Classifications: M31, R41